First choice leading international designers select the best of their own work - Cato, Ken (Craftsman House, 1996)
"First Choice Second Edition is a continuing opportunity to learn how the world's top designers approach and evaluate their work. In an attempt to demonstrate the broad parameters of design, Ken Cato has selected a cross-section of graphic media styles from many countries. As a result, First Choice Second Edition is an invaluable reference book for those interested in graphic design and the selection criteria for quality applied to the world's leading exponents of the profession."--Jacket